Perancangan Desain Karakter untuk Buku Ilustrasi Anak tentang Gaya Hidup Minim Sampah - Afifah, Annisa Fitri; Ayuswantana, Alfian Candra; Masnuna, Masnuna (Universitas Pahlawan Tuanku Tambusai, 2024)
Indonesia produces huge amounts of garbage every year and most of it comes from poorly managed household waste, which has a negative impact on the environment. One way to reduce garbage is to adopt a zero waste lifestyle, and it's good that this lifestyle has been taught from an early age, especially in the elementary school age. Zero waste lifestyle concepts can be taught to children using an interesting medium, one of which is children's illustration books. Childern illustration books need an interesting character in them to help the reader understand the content of the story and become an element that attracts the child to continue reading. Character design design uses qualitative research methods by conducting interviews, observations, and questionnaires. Through interviews already conducted with 9-12-year-olds, they preferred funny character designs with big eyes and propositional body shapes.